The concept of bridge substructure planning using Revit application for BIM approach - Lubis, Ahmad Mawardi; Rifai, Andri Irfan; Sari, Yusra Aulia; Handayani, Susanty (Indonesian Journal of Multidisciplinary Science, 2024)
Bridges are a very important infrastructure in a country. Bridges function as links between roads cut off by one obstacle, such as valleys, rivers, lakes, and irrigation canals. In this paper, the author will model the planning of the bridge understructure using Revit Software as a form of BIM technology. The modelling that will be carried out includes bridge abutments and piles as foundations. The material used in modelling the lower structure of the bridge in this article is concrete. As a result, the completed modelling can be viewed with details such as 3D view, top view, side view, front view, and also dimensions. So, it can be concluded that the use of BIM technology is very helpful and makes it easier for engineers to implement a construction project.